Microsoft SQL Server 2008 R2 Unleashed - Rankins, Ray (Pearson Education, 2011)
This is the industry’s most comprehensive and useful guide to SQL Server 2008 and 2008 R2. It presents start-to-finish coverage of SQL Server’s core database server and management capabilities, plus complete introductions to Integration, Reporting, and Analysis Services, application development, and much more.